The Tax Avoidance Practice of Indonesian Mining Companies - Lestari Adhi Widyowati; Inta Hartaningtyas Rani; Jara Hardiyanti Jalih (Jurnal Proaksi, 2024)
The mining sector in Indonesia is one of the most significant contributors to state revenue through taxation. The mining industry contributed 33.431 trillion in the first semester of 2019. Although the amount seems significant, it would be bigger if mining companies did not avoid paying taxes. This research aims to analyze the role of institutional ownership in moderating the influence of profitability, thin capitalization, and inventory intensity on tax avoidance. This research uses MRA to analyze data on mining companies listed on the IDX from 2018 -2022. Data was collected from the population using purposive sampling to produce 60 samples. The research results show that profitability and thin capitalization variables impact tax avoidance, while inventory intensity differs. Institutional ownership moderates the impact of low profitability and thin capitalization on tax avoidance. However, there is no proof that this lessens the effect of inventory intensity on tax avoidance. By choosing a group of variables that affect tax avoidance, this study fills a knowledge gap in the influence of institutional ownership as a moderating variable. Future research can replicate this research by expanding the industry that is the object of research, extending the period, and using different analysis tools.